Integrating Animated Videos, Songs, and Games to Enhance Young Learners’ Vocabulary Learning in EFL Classrooms: A Descriptive Study in Thai Elementary School - Riyanto, Raditya Ferdi; Astutik, Yuli; Agustina, Sheila; Mongboon, Nantana; Pribadi, Imam (ELLITE: Journal of English Language, Literature, and Teaching, 2025)
This study aimed to explore how animated educational videos, song clips, and audiovisual game-based learning support vocabulary acquisition, interaction, and active participation among fourth-grade students in an EFL classroom. Using a descriptive qualitative design, the research was conducted in a Thai elementary school with 22 students aged 9-10. Data were collected over seven English lessons through structured non-participant observations and detailed field notes, focusing on behavioral indicators of engagement, understanding, and peer collaboration. Research findings revealed that animated videos helped clarify abstract vocabulary through visual storytelling and repetition, while song clips promoted memorability and emotional involvement through rhythm and movement. Audiovisual games, on the other hand, encouraged sustained focus, classroom interaction, and vocabulary application through playful, feedback-rich activities. Each tool contributed uniquely to different stages of learning, highlighting the value of varied, multimodal media use. This study offers practical insights into how thoughtfully integrated audiovisual tools can enrich English instruction for young learners. It encourages educators to strategically align media types with lesson goals and learner characteristics, particularly in environments with limited access to authentic English use.